From Negligence to Resistance: Danish Welfare in the Light of Free-Movement Law. Issue 2 (June 2016) - Jacqueson, Catherine
The Danish welfare system is famous for being a universal system covering all residents with generous benefits financed through general taxes. This is at least true for benefits such as social assistance, health care and the state retirement pension which are discussed here. This article analyses the implications of EU free movement law on residence-based welfare rights in Denmark. It argues that EU law has not led to major legal and policy changes. Yet Denmark has been quick off the mark in picking up on EU restrictions and in erecting safeguards for residence-based schemes as demonstrated by the discussion of the state-retirement pension and social assistance in this article. On the other hand, it has been slow in implementing EU law on extending health cover to scheduled treatments received in other Member States. While the Danish position has, for a long time, been that EU law does not affect the Danish welfare model, public discourse has recently changed with allegations of EU law leading to social dumping and benefit tourism. This article concludes that a search for a legal balance between free movement and national welfare is still in the making.